Why should support schemes for renewable electricity complement the EU emissions trading scheme? - Lehmann, Paul; Gawel, Erik (Energy policy, 2013)
In virtually all EU Member States, the EU Emissions Trading Scheme (EU ETS) is complemented by support schemes for electricity generation from renewable energy sources (RES-E). This policy mix has been subject to strong criticism. It is mainly argued that RES-E schemes contribute nothing to emissions reduction and undermine the cost-effectiveness of the EU ETS. Consequently, many scholars suggest the abolition of RES-E schemes. However, this conclusion rests on quite narrow and unrealistic assumptions about the design and performance of markets and policies. This article provides a systematic and comprehensive review and discussion of possible rationales for combining the EU ETS with RES-E support schemes. The first and most important reason may be restrictions to technology development and adoption. These may be attributed to the failure of markets as well as policies, and more generally to the path dependency in socio-technical systems. Under these conditions, RES-E schemes are required to reach sufficient levels of technology development. In addition, it is highlighted that in contrast to the EU ETS RES-E support schemes may provide benefits beyond mitigating climate change. ► The EU ETS addresses policy objectives appropriately under narrow assumptions only. ► Deviations from these assumptions may justify RES-E support schemes. ► First rationale: technology choices are distorted by market and policy failures. ► These failures are aggravated and perpetuated by socio-technical path dependencies. ► Second rationale: RES-E schemes address goals beyond mitigating climate change.